Pengaruh Metode Kisah dalam Pembelajaran PAI terhadap Prestasi Belajar Siswa di SMP Al-Munawwir Sangatta Selatan - M, Faturrahman; Mubarok, Ramdanil; Faruk Fauzi, Muhammad Ibnu (Green Publisher Indonesia, 2025)
This study aims to determine the extent of the influence of the storytelling method in Islamic Religious Education (PAI) learning on students' academic achievement at SMP Al-Munawwir, South Sangatta. A quantitative approach was employed, with data collected through questionnaires, classroom observations, and supporting documentation. The sample consisted of 56 students from grades VII to IX, selected using simple random sampling. The data were analyzed using simple linear regression with the assistance of SPSS software. The analysis results showed a Pearson correlation value of r = 0.412, categorized as moderate, with a coefficient of determination of 41.2%. This indicates that the storytelling method in PAI learning contributes significantly to improving students' learning outcomes, while the remaining 58.8% is influenced by other unexamined factors. The resulting regression equation is Y = 11.591 + 0.227X, which can be used to predict academic improvement based on the application of storytelling. These findings demonstrate that the storytelling method is an effective pedagogical approach for enhancing students’ understanding of Islamic teachings and increasing their academic achievement in religious education.